PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Trianingrat, Ni komang Ayu Rikha; Supartha, I Wayan Gede (E-Jurnal Manajemen, 2020)
Work performance or performance s the result of quality and quantity of work achieved by an employee n carrying out their duties n accordance with the responsibilities given. The number of samples n this study were 60 respondents. Data collection was obtained from the results of the distribution of questionnaires with ndicators measured by Likert Scale. Data analysis n this study uses path analysis. The results of this study ndicate that 1) The results of this study ndicate that work stress has a negative nfluence on employee performance, 2) work stress has a negative effect on work motivation. 3) work motivation has a positive effect on employee performance. 4) work motivation acts as a mediator on the effect of work stress on employee performance. The company should pay attention to the tasks and responsibilities given to employees with the ability of employees so that employees do not feel stressed and can mprove performance and the company pays attention to the time employees are completing work Keywords: job stress, employee performance, and work motivation